Cavitands as Containers for α, ω‐Dienes and Chaperones for Olefin Metathesis. Issue 46 (24th October 2018) - Wu, Nai‐Wei; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula; Yu, Yang; Rebek, Julius
Abstract: Described herein is the behavior of α, ω‐dienes sequestered within cavitands in aqueous (D2 O) solution. Hydrophobic forces drive the dienes into the cavitands in conformations that best fill the available space. Shorter dienes (C9 and C10) bind in compressed conformations that tumble rapidly in the cavitands. Longer dienes induce capsule formation between cavitands with self‐complementary hydrogen bonding sites, where the dienes exist in extended conformations. In cavitands unable to form capsules, longer dienes adopt folded structures. The wider open ends allow the synthesis of medium‐sized cycloalkenes by ring‐closing metathesis reactions with the Hoveyda–Grubbs‐II catalyst. Yields of cycloheptene and cyclooctene were enhanced by the chaperones in water when compared with reactions of the free dienes in either aqueous media or chloroform, and even cyclononene could be prepared within the cavitand. Abstract : Rough and tumble : Hydrophobic forces drive α, ω‐dienes into cavitands in conformations that best fill the available space. Shorter dienes (C9 and C10 ) bind in compressed conformations that tumble rapidly within the cavitands. The cavitands enhanced the synthesis of medium‐sized cycloalkenes by ring‐closing metathesis compared with reactions of the free dienes in either aqueous media or chloroform.